Interplay Between N6-Methyladenosine (m6A) and Non-coding RNAs in Cell Development and Cancer - Fazi, Francesco; Fatica, Alessandro (Frontiers in Cell and Developmental Biology, 2019)
RNA chemical modifications in coding and non-coding RNAs are known from decades. They are generally installed by specific enzymes and, in some cases, they can be read and erased by other specific proteins. The impact of RNA chemical modifications on gene expression regulation and the reversible nature of some of these modifications led to the birth of the word epitranscriptomics, in analogy with the changes that occur on DNA and histones. Among more than 100 different modifications identified so far, most of the epitranscriptomics studies focused on the N6-methyladenosine (m6A), which is the more abundant internal modification in protein coding RNAs. m6A can control several pathways of gene expression, including spicing, export, stability and translation. In this review, we describe the interplay between m6A and non-coding RNAs, in particular microRNAs and lncRNAs, with examples of its role in gene expression regulation. Finally, we discuss its relevance in cell development and disease.